Marketing strategy for a late follower in mass spectrometry equipment - Reyes, Julio Rodrigo J. (University of the Philippines Diliman, Technology Management Center, 2013)
Shimadzu Philippines Corporation (SPC) is a direct subsidiary of Shimadzu Corporation Japan tasked to handle the sales, marketing and after-sales-support of the Shimadzu product in the Philippines.